Energy Efficiency Analysis of Computing Equipment: A Case Study at the Faculty of Engineering, Udayana University - I Ketut Adi Junantara; I Nyoman Satya Kumara; Wayan Gede Ariastina (Journal of Social Research, 2025)
Energy efficiency in universities is a crucial component of national and regional strategies to reduce energy consumption and environmental impact. This is supported by regulations such as Presidential Regulation No. 33/2023 and the Bali Governor's Circular Letter, as well as the Bali Clean Energy Program, which promotes the use of energy-saving devices and renewable energy in the education sector. This study employs a descriptive quantitative approach, conducting a comprehensive inventory and direct observation of 609 computing devices at the Faculty of Engineering, Udayana University, Jimbaran. Data analysis includes statistical descriptive methods and interviews to evaluate compliance with the Energy Star standard and alignment with existing energy policies. The inventory revealed that 74% (448 units) of the computing devices (desktops, laptops, printers, scanners) were Energy Star certified. However, a significant implementation gap was identified, as all network devices (routers and access points) and projectors (totaling 161 units) lacked energy efficiency certifications. The estimated annual energy consumption cost for these devices ranges from approximately Rp 106 million (under a 4-hour usage scenario) to Rp 218 million (under an 8–10 hour usage scenario). While adherence to energy efficiency standards is high for core computing equipment, there is a notable gap in policy implementation for peripheral devices like projectors and network infrastructure. The study recommends the proactive procurement of energy-efficient devices across all categories and the implementation of periodic energy audits to enhance sustainability efforts and achieve significant cost savings within the university.